39. THE PSYCHOLOGY OF MEN AND WOMEN IN ACCORDANCE QURAN AND SUNNAH - Umar, Mukhtar Ibrahim (Journal of Islamic, Social, Economics and Development, 2024)
This research aims to explain the important aspects related to the psychological aspects between men and women as mentioned in the Qur’an and Sunnah. This research deals with the nature of men and women with regard to marital life, in addition to mentioning the individual differences between them and the impact of that on marital cohabitation and family life. The main goal of this research is to study the psychological and biological differences between men and women with evidence from the Prophet’s hadiths while strengthening them with verses from the Noble Quran. The research adopts the inductive approach and Analytical approach to trace and extrapolate texts and other sources related to social psychology and family psychology, in addition to that, it mentions the relationship between individual differences of men and women in contemporary marital life. The research will address several aspects, namely: psychological nature of men and women, level of mental abilities and skills of men and women, level of sensory perception of men and women, characteristics of women in physical functions, psychological and physical symptoms, how to deal with the wife. The research concluded that there are individual differences between men and women, and knowing that is one of the important matters recognized by Islamic law and considered in the legal rulings, furthermore; mastering that has a positive impact on the management of marital cohabitation and family life.